Pathogen detection and antibiotic use in granulomatous lobular mastitis: a comparison of mNGS and culture - Mu, Xu; Luo, Hongmin; Li, Hanhua; Chen, Shenghua; Han, Yuyang; Zhang, Lin; Liu, Wei; Qiao, Weilong; Zheng, Shaoyi; Huang, Zhifeng (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aimed to evaluate the clinical microbial profile of patients with granulomatous lobular mastitis (GLM) and compare various detection methods to identify the most effective approach for pathogen detection, which could help enhance clinical diagnosis and treatment.MethodsWe retrospectively analyzed data from 84 patients diagnosed with GLM, assessed the composition of pathogenic microorganisms in these patients, and compared the effectiveness of different sampling methods and detection techniques.ResultsCorynebacterium kroppenstedtii (C. kroppenstedtii) was identified as the predominant microorganism among GLM patients. The positivity rate was low in skin swabs (10%) but similar in pus (40%) and tissue samples (37%). After antibiotic treatment, the pathogen detection rate of metagenomic next-generation sequencing (mNGS) (54.55%) was found to be higher than that of culture-based methods (27.27%). Among the GLM cases with pathogenic infection, although mNGS demonstrated higher sensitivity (75.0%) than culture tests (50.0%), both methods exhibited 100.0% specificity. However, the time for obtaining results with mNGS was significantly shorter (1.2 ± 0.41 days) compared to bacterial culture (5.5 ± 0.64 days) (P < 0.05).ConclusionsOur findings indicate that pus was the most suitable sample type for microbial evidence collection in patients with GLM. mNGS demonstrated superior performance compared to culture in distinguishing infectious from non-infectious cases, with reduced antibiotic interference, faster turnaround time, and higher accuracy. Based on our single-center experience, empirical cephalosporin treatment may be appropriate for these patients. Additionally, surgical intervention remains the most efficient approach for rapid and complete resolution.